Penerapan Pembelajaran Dengan Strategi Mind Mapping Dalam Meningkatkan Hasil Belajar Siswa Pada Materi Sistem Reproduksi Manusia Kelas IXA SMPN 1 Tanjung Jabung Timur - walhadia, walhadia (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The purpose of this study is to improve student learning outcomes in the material of the human reproductive system. The study was conducted in class IX A in SMP N 1 Tanjung Jabung TimurÂ  Middle School in the 2018/2019 learning year. This study is a Classroom Action Resesarch adapted from the Kemis and Tagar PTK models, which consists of 4 stages, namely: 1) planning, 2) implementation, 3) observation and 4) reflection. The results of this study indicate an increase significant in the first cycle and second cycle for the assessment of learning outcomes and the ability of students to make mind mapping on the material of the human reproductive system. Based on the results of the research obtained it can be concluded that mind mapping learning strategies can improve learning outcomes and develop psychometric skills of students to create and read mind mapping.